2020
DOI: 10.7717/peerj.9099
|View full text |Cite
|
Sign up to set email alerts
|

Application of 16S rRNA gene sequencing in Helicobacter pylori detection

Abstract: Helicobacter pylori is one of the major stomach microbiome components, promoting development of inflammation and gastric cancer in humans. H. pylori has a unique ability to transform into a coccoidal form which is difficult to detect by many diagnostic methods, such as urease activity detection, and even histopathological examination. Here we present a comparison of three methods for H. pylori identification: histological assessment (with eosin, hematoxylin, and Giemsa staining), polymerase chain reaction (PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 62 publications
0
19
0
1
Order By: Relevance
“…PCR can be considered as either an invasive or non-invasive method for detecting H. pylori depending on the applied material. It demonstrates up to 95% sensitivity and 95% specificity [38]. Molecular methods are more expensive than other methods, and the laboratory must have appropriate equipment and experience.…”
Section: Molecular Invasive and Non-invasive Methods For H Pylorimentioning
confidence: 99%
“…PCR can be considered as either an invasive or non-invasive method for detecting H. pylori depending on the applied material. It demonstrates up to 95% sensitivity and 95% specificity [38]. Molecular methods are more expensive than other methods, and the laboratory must have appropriate equipment and experience.…”
Section: Molecular Invasive and Non-invasive Methods For H Pylorimentioning
confidence: 99%
“…Our study supports and extends, using an expanded sample size and the number of routine tests, a previous Polish study of 40 patients who were tested with histological assessment, polymerase chain reaction (PCR) detection of urease ( ureA specific primers), and 16S rRNA gene sequencing. They reported that 17.5% of infections were detected by only 16S rRNA sequencing but not with PCR or histology/IHC methods 25 . A recent Spanish study reported that using droplet digital polymerase chain reaction detected low‐density H .…”
Section: Discussionmentioning
confidence: 99%
“…logical assessment, polymerase chain reaction (PCR) detection of urease (ureA specific primers), and 16S rRNA gene sequencing. They reported that 17.5% of infections were detected by only 16S rRNA sequencing but not with PCR or histology/IHC methods 25. A recent Spanish study reported that using droplet digital polymerase chain reaction detected low-density H. pylori infection in 36% of patientsF I G U R E 1 ROCcurve of Helicobacterpylori detection based on 16S rRNA operational taxonomic units (OTUs, red line) Abbreviations: 16S rRNA, 16S ribosomal ribonucleic acid; HpN, H. pylori-negative; HpP, H. pyloripositive; OTUs, operational taxonomic units; RA, relative abundance.…”
mentioning
confidence: 99%
“…PCR including the assay targeting the 16S rRNA gene confirmed to be a far more sensitive method for H pylori detection in gastric biopsies compared to other methods 18 …”
Section: Invasive Testsmentioning
confidence: 98%